Photoacoustic imaging of clinical metal needles in tissue - Su, Jimmy (Society of Photo-Optical Instrumentation Engineers, 2010)
The ability to visualize and track temporarily or permanently implanted metal devices is important in many applications ranging from diagnosis to therapy. Specifically, reliable imaging of metal needles is required in today’s clinical settings. Currently, ultrasound is utilized to image a needle inserted into tissue in real time. However, the diagnostic value and tracking ability of these images depends highly on the orientation of the needle, and also its proximity to regions of interest in the tissue. We examine the use of photoacoustic imaging combined with current ultrasound imaging methods to obtain high-contrast images of commonly used needles in the body. Experiments were performed using 21 G and 30 G needles inserted into ex vivo porcine tissue and tissue-mimicking phantoms. The needles and surrounding tissue were imaged using an ultrasound imaging system interfaced with the pulsed laser source necessary for photoacoustic imaging. The results suggest that photoacoustic imaging, combined with ultrasound imaging, is capable of real-time, high-contrast, and high-spatial-resolution visualization of metal implants within anatomical landmarks of the background tissue.